Optimization of a vacuum spark discharge as an X-ray source - Bashutin, O.A.; Vovchenko, E.D.; Savjolov, A.S.; Sarantsev, S.A. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The paper reports on the results of experimental investigation of the influence of the trigger location relative to the discharge gap and the trigger energy on spatial and temporal stability and emission parameters of the X-ray sources, formed in low-inductance vacuum spark discharge. The investigations corroborated the influence of initial plasma characteristics on vacuum spark evolution. The conditions for primary forming of the hot spots radiating the X-ray within the spatial region less than 500 μm and with a temporal jitter less than 300 ns were defined. Представлены результаты экспериментального исследования влияния расположения триггера относительно разрядного промежутка и энергетики триггера на пространственную и временную стабильность эмиссионных параметров источников рентгеновского излучения, образующихся в низкоиндуктивном вакуумном искровом разряде. Подтверждено влияние характеристик инициирующей плазмы на эволюцию вакуумной искры. Определены условия для преимущественного формирования горячих точек, испускающих рентгеновское излучение, в пределах локальной области размером менее 500 мкм с временным разбросом менее 300 нс. Представлено результати експериментального дослідження впливу розташування триггера щодо розрядного проміжку й енергетики тригера на просторову і часову стабільність емісійних параметрів джерел рентгенівського випромінювання, що утворюються в низькоіндукційному вакуумному іскровому розряді. Підтверджено вплив характеристик ініціюючої плазми на еволюцію вакуумної іскри. Визначено умови для переважного формування гарячих точок, що випускають рентгенівське випромінювання, у межах локальної області розміром менш 500 мкм із часовим розкидом менш 300 нс.